Genetically-engineered "all-in-one" vaccine platform for cancer immunotherapy - Aihua Wu; Yingzhi Chen; Hairui Wang; Ya Chang; Meng Zhang; Pengfei Zhao; Yisi Tang; Qin Xu; Zhuangzhi Zhu; Yang Cao; Yongzhuo Huang (Elsevier, 2021)
An essential step for cancer vaccination is to break the immunosuppression and elicit a tumor-specific immunity. A major hurdle against cancer therapeutic vaccination is the insufficient immune stimulation of the cancer vaccines and lack of a safe and efficient adjuvant for human use. We discovered a novel cancer immunostimulant, trichosanthin (TCS), that is a clinically used protein drug in China, and developed a well-adaptable protein-engineering method for making recombinant protein vaccines by fusion of an antigenic peptide, TCS, and a cell-penetrating peptide (CPP), termed an "all-in-one" vaccine, for transcutaneous cancer immunization. The TCS adjuvant effect on antigen presentation was investigated and the antitumor immunity of the vaccines was investigated using the different tumor models. The vaccines were prepared via a facile recombinant method. The vaccines induced the maturation of DCs that subsequently primed CD8+ T cells. The TCS-based immunostimulation was associated with the STING pathway. The general applicability of this genetic engineering strategy was demonstrated with various tumor antigens (i.e., legumain and TRP2 antigenic peptides) and tumor models (i.e., colon tumor and melanoma). These findings represent a useful protocol for developing cancer vaccines at low cost and time-saving, and demonstrates the adjuvant application of TCS-an old drug for a new application.